Avaliação dos efeitos agudos da cetamina no comportamento, estresse oxidativo e eletroencefalograma em modelo de depressão-símile induzido por dexametasona em ratos adultos - Borges, Lucas Teixeira Nunes (2023)
Major Depressive Disorder (MDD) is a serious psychiatric illness of deep public health concern. The currently available antidepressants are associated with several limitations, including the long therapeutic initiation. In this regard, ketamine (KET) is presented as an alternative with rapid antidepressant action. Thus, the aim of the study was to evaluate the acute behavioral, oxidative stress and electroencephalographic effects of ketamine in a dexamethasone (DEX)-induced depression-like model in adult rats. For this, adult male Wistar rats weighing between 250-350g were used. Initially, a study was carried out to select the dose of DEX to induce depression-like. After this step, the animals were treated with DEX at a dose of 1.5 mg/kg for 14 days subcutaneously (SC) and acutely treated with KET at a dose of 10 mg/kg intraperitoneally (IP) on the last day of treatment; after two hours, the open field, forced swimming, elevated plus maze, sucrose preference, oxidative stress and electroencephalogram (EEG) tests were performed. The results showed that the anxiogenic and depression-like effects induced by DEX were reversed by KET in the elevated plus maze, forced swimming and sucrose preference tests. KET also reversed the DEX-induced increase in malondialdehyde levels in the hippocampus. DEX management reduced the high beta wave. On the other hand, KET alone increased the theta band, showing antidepressant effect on EEG. In conclusion, the results demonstrated antidepressant, anxiolytic and lipid peroxidation reduction effects of ketamine. Thus, this study collaborates with the redirection of ketamine as a rapid antidepressant drug.